Neurofeedback - Jaber, Abrar Hasan; Al-Hilo, Buthaina Mansour (Al-Adab Journal, 2021)
The Neurofeedback technique is one of the most prominent, modern and developed therapeutic techniques based on mindfulness. There have been several studies searching for the extent of its impact as a form of effective conditioning of the brain’s electrical activity, which enhances positive activity by acting and preventing the emergence of negative activity, and working on changing the surface of brain cells, which affects the effectiveness of the brain and improving the performance of cognitive therapies in it. Different patterns of electrical activity can be identified by placing electrodes on the scalp and recording those cortical activities of the nearby brain regions -known as brain waves- and through capacities and frequencies the different frequency components in the brain are categorized into delta waves, theta, alpha, beta, and Gama, each one representing a certain physiological function and any defect in it represents various symptoms of mental disorders, so the reorganization of these waves helps to recover from these symptoms. There are different types of neurological feedback, including superficial neural feedback, used to change the amplitude or speed of certain brain waves in certain locations of the brain to treat a specific disorder, and slow cortical nerve feedback to improve the direction of slow cortical potentials, and neurological feedback data provides responses or observations about blood flow to the brain, and it also presents a continuous comparison of changes in the electrical activity in the brain with a systematic database to provide continuous feedback. The functional magnetic resonance imaging technology “fMRI” is the latest type of neural feedback to regulate brain activity based on the activity feedback from the deep cortical regions of the brain.